Successful Treatment of Antibiotic-resistant, Poly-microbial Bone Infection With Bacteriophages and Antibiotics Combination. (14th March 2019) - Nir-Paz, Ran; Gelman, Daniel; Khouri, Ayman; Sisson, Brittany M; Fackler, Joseph; Alkalay-Oren, Sivan; Khalifa, Leron; Rimon, Amit; Yerushalmy, Ortal; Bader, Reem; Amit, Sharon; Coppenhagen-Glazer, Shunit; et al.
Abstract: A patient with a trauma-related left tibial infection associated with extensively drug-resistant Acinetobacter baumannii and multidrug-resistant Klebsiella pneumoniae was treated with bacteriophages and antibiotics. There was rapid tissue healing and positive culture eradication. As a result, the patient's leg did not have to be amputated and he is undergoing rehabilitation.